Proceso de atención de enfermería en adulta mayor con VIH y neumonía asociada a Covid-19. - Santillán Vera, Jean Carlos (2021)
The present clinical case that was carried out at the Guasmo Sur General Hospital belongs to a female patient, 66 years of age, with a diagnosis of HIV, since 4 years ago positive, according to hospital records, he received antiretroviral medication 2 years ago, all this The medical history refers, today he enters the emergency area in an ambulance without company. Oriented in space, time, person and place, presenting a picture of dyspnea on medium efforts plus unquantified thermal rise, with intense headache, dyspnea progresses at minimal efforts, tachypnea and desaturating at 95%, cough, in the first instance specifically, six days ago She was treated in this same unit in the outpatient area, but her picture has been complicated for 24 hours, the environment is evaluated by the infectious disease service with antibiotic therapy to be defined, a chest tomography with diffuse infiltrate, bilateral in patches is obtained compatible with pneumonia, viral associated with covid-19, which the admission process is carried out, nursing care is provided based on the basic principles of control, patient care, plus the relevant intervention based on the affected needs that present the patient to provide quality, care, and control of risks that these pathologies present to health, we proceed to control, monitoring of vital signs, 99% oxynotherapy, channeling, control and fluid balance, achieving the results obtained that stabilize the patient by applying the appropriate nursing care, until she is referred to the intensivist doctor to carry out what is pertinent to the case.